TURKEY NESTING SUCCESS OM A FLORIDA STUDY AREA - Lovett E. Williams Jr.; David H. Austin; Tommie E. Peoples (Wildlife Society Bulletin)
Abstract Nesting success of wild turkeys (Meleagris gallopavo) was measured for 108 nests of radio‐tracked hens on a Florida study area during an 8‐year period. During 4 years of the study, poisoned eggs were distributed in a part of the study area to measure their effect in reducing nesting losses and to obtain carcasses of predators for identification. Most predation was by 4 mammal species; several potential predators, including feral hogs (Sus scrofa), common crow (Corvus corvus), and armadillo (Dasypus novemcinctus) were not significantly involved. Nesting success was 59% in 4 of the years when no poisoned eggs were distributed and 72% during 4 years in the treated area. A high rate of compensatory nesting was detected, the effect of which would probably negate any advantages of such a control effort.